Love never dies - Lloyd Webber, Andrew, 1948- (Hal Leonard, 2018)
The sequel to "the Phantom of the Opera" is set in America in Coney Island, ten years later. Coney Island is a fantastic place, the great eighth wonder of the world. It was the place where all the freaks and oddities went and of course the "Phantom" could be absorbed there. He's gone with Madame Gieru, his old friend, and with Meg, her daughter. He's now the big mogul of Coney and is now running the whole place and that's where the story starts.